High‐Performance High‐Loading Lithium–Sulfur Batteries by Low Temperature Atomic Layer Deposition of Aluminum Oxide on Nanophase S Cathodes. Issue 17 (18th May 2017) - Meng, Xiangbo; Liu, Yuzi; Cao, Yanqiang; Ren, Yang; Lu, Wenquan; Elam, Jeffrey W.
Abstract : This study examines the effects of nanophase S and surface coatings via atomic layer deposition (ALD) on high‐loading sulfur cathodes for developing high‐performance and high‐energy lithium–sulfur (Li–S) batteries. It is first verified that ball milling is an effective and facile route for nanoengineering microsized S powders and the resultant nanoscale S particles exhibit better performance. Using these ball milled nanoscale S cathodes, it is found that ALD Al2 O3 performed at 50 °C yields deposits that evolve with ALD cycles from dispersed nanoparticles, to porous, connected films, and finally to dense and continuous films. Moreover, this low temperature ALD process suppresses S loss by sublimation. The ALD Al2 O3 greatly improves sulfur cathode sustainable capacity and Coulombic efficiency. This study postulates two different mechanisms underlying the effects of ALD Al2 O3 surface coatings depending on their morphology. ALD Al2 O3 nanoparticles dispersed on the sulfur surface mainly function to adsorb polysulfides, thereby inhibiting S shuttling and improving sustainable capacity and Coulombic efficiency. By contrast, ALD Al2 O3 films behave as a physical barrier to prevent polysulfides from contacting the liquid electrolyte and dissolving. The dispersed Al2 O3 nanoparticles improve both sustainable capacity and Coulombic efficiency while the closed Al2 O3 films improve Coulombic efficiency while decreasing the capacity. Abstract : Nanophase S particles from ball milling of microsized S powder are combined with surface coating of Al2 O3 via low‐temperature atomic layer deposition (ALD). The ALD Al2 O3 evolves with ALD cycles from dispersed nanoparticles, to porous, connected films, and finally to dense and continuous films. The result is high performance Li–S batteries at high S loading.